1981
DOI: 10.1111/j.1365-2125.1981.tb01299.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative comparison of aldosterone antagonists in normal human subjects: prediction of therapeutic potency.

Abstract: 1 The potency of single doses of the aldosterone antagonist SC8109 relative to spironolactone in reversing the urinary electrolyte effects of fludrocortisone was examined in a double-blind, balanced, crossover study in six healthy volunteers. 2 For the urinary ratio log10 10 Na/K, the relative potency of SC8109: spironolactone on a weight basis was 0.08:1 (95% confidence limits 0.04-0.13:1). 3 The potency of SC8109 relative to spironolactone for natriuresis and antikaliuresis was 0.10:1 and 0.05:1, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

1982
1982
1982
1982

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…In general, the urinary electrolyte findings confirm our previous experience with the drugs (McInnes et al, 1981). The natriuretic potency of prorenoate potassium relative to spironolactone (3.6, 95% confidence limits, 1.6-10.4) was neither statistically inconsistent with the results from the dose-ratio approach (4.2, 95% confidence limits, 2.7-6.9) (McInnes et al, 1981) nor contraindicated a two-fold increase in relative potency with regard to single dose studies (Ramsay et at., 1975a, b).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In general, the urinary electrolyte findings confirm our previous experience with the drugs (McInnes et al, 1981). The natriuretic potency of prorenoate potassium relative to spironolactone (3.6, 95% confidence limits, 1.6-10.4) was neither statistically inconsistent with the results from the dose-ratio approach (4.2, 95% confidence limits, 2.7-6.9) (McInnes et al, 1981) nor contraindicated a two-fold increase in relative potency with regard to single dose studies (Ramsay et at., 1975a, b).…”
Section: Discussionsupporting
confidence: 89%
“…The wide confidence limits of this estimate indicate its imprecision, a consequence of the shallow aldosterone antagonist dose-response trends. It seems unlikely that this resulted from excessive mineralocorticoid challenge in view of the results for urinary sodium excretion and the similar potassium responses with lower doses of fludrocortisone in previous studies (McInnes et al, 1981;Ramsay et al, 1977a). At steady state, dose-responses for potassium excretion may indeed be shallow or confounding homeostatic influences may conceal the true relationship.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Likewise, relating the findings from single dose studies to the clinical situation where the drug is prescribed continuously and maximal activity is observed only after some days medication, should be cautious. However, repeated dosing studies in healthy subjects have confirmed dissociation of urinary sodium and potassium handling (McInnes et al, 1981a;Ramsay et al, 1977). The relatively narrow dose range over which the steep portion of the potassium excretion relationship is encountered may explain the difficulties in discriminating between the urinary potassium responses to different doses of spironolactone in those studies.…”
Section: Discussionmentioning
confidence: 99%